PENGARUH MODEL PEMBELAJARAN KOOPERATIF TGT BERBANTUAN MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR IPAS KELAS IV SEKOLAH DASAR - Kembar Wardaniasih, Luh; Yudiana, Kadek; Herya Darma Utami , Ketut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by a learning process that is insufficiently interactive, boring, and lacking in innovation, as well as the suboptimal integration of learning media, which results in students lacking the desire and motivation to learn. The purpose of this study is to determine the effect of the interactive multimedia-assisted TGT cooperative learning model on the learning outcomes of fourth-grade elementary school students in Integrated Science. This study is a quasi-experimental study using a Non-Equivalent Post-test Only Control Group Design. The study population consisted of all fourth-grade students in Cluster IV of Kubutambahan Subdistrict, with the sample determined using cluster sampling. Data collection employed an objective test comprising 30 items. Hypothesis testing was conducted using an Independent Samples t-test. The results obtained by the researcher were a calculated t-value of 2.732 and a critical t-value of 1.677, such that the calculated t-value was greater than the critical t-value (2.732 > 1.677), with a significance level (two-tailed) of 0.009 < 0.05. The conclusion drawn is that there is a significant effect, indicating that H₀ is rejected and H₁ is accepted.